THE FORMATION OF THE CITY OF MARGILAN (OLD MARGILAN) IN THE HISTORY OF ARCHITECTURE - Muminova , Nigoraxon Zokhidovna (Educational Research in Universal Sciences, 2024)
The article highlights opinions and proposals on measures to preserve housing that have survived in the architectural history of the city of Margilan to this day, and their application.